Unveiling the Essence of Charity and Worship: A Thematic Study of Surah Al-Ma'un - Alle, Kuthar Gabar Zedin; Muyhaldeen, Noorkahleed; Hussein, Sikna Jebur (Dzil Majaz: Journal of Arabic Literature, 2025)
The Qur’an is the primary source of guidance and spiritual development in Islam, and its reflective contemplation is essential for shaping a believer’s character. Among its chapters, Sūrat al-Māʿūn stands out—despite its brevity—for its profound themes related to faith, ethics, and social behavior. The research problem arises from a noticeable neglect in giving adequate scholarly attention to shorter sūrahs, including al-Māʿūn, which are often underestimated due to their concise nature. This study aims to uncover the deeper moral, theological, and social meanings embedded in Sūrat al-Māʿūn, especially its warnings against hypocrisy and disbelief. The study employs a qualitative, analytical method, drawing from classical and contemporary Qur’anic exegesis to offer a thematic and structural analysis of the sūrah. It seeks to bridge traditional interpretations with modern analytical frameworks, making the message of the sūrah relevant to today’s ethical and spiritual challenges. The results highlight al-Māʿūn as a rich text that presents a clear critique of superficial religiosity and unethical social behavior. The contribution of this study lies in its effort to reawaken interest in the thematic depth of shorter Qur’anic chapters and demonstrate their critical role in spiritual education and moral reform